2017
DOI: 10.1080/14767058.2017.1297404
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for predicting spontaneous preterm birth: an umbrella systematic review

Abstract: Cervical fetal fibronectin, alpha fetoprotein, C- reactive protein and interleukin 6 can have an overall good diagnostic accuracy in identifying pregnancies at risk of SPTB. Large prospective studies in different sub-set of women are needed to ascertain whether the combination of different serological and imaging marker can improve antenatal prediction of this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 24 publications
2
37
1
3
Order By: Relevance
“…IL-6 is induced in decidual tissues at term in labor compared to not in labor (45) and therefore part of parturition. Nevertheless, while increased IL-6 levels were detected in maternal or fetal blood or amniotic fluid, this cytokine is also a well-established marker with an overall good diagnostic accuracy in identifying pregnancies at risk of spontaneous PTB (46)(47)(48). This is in agreement with our findings since the patients in our study delivering preterm had enhanced IL-6 level in plasma.…”
Section: Figure 3 |supporting
confidence: 92%
“…IL-6 is induced in decidual tissues at term in labor compared to not in labor (45) and therefore part of parturition. Nevertheless, while increased IL-6 levels were detected in maternal or fetal blood or amniotic fluid, this cytokine is also a well-established marker with an overall good diagnostic accuracy in identifying pregnancies at risk of spontaneous PTB (46)(47)(48). This is in agreement with our findings since the patients in our study delivering preterm had enhanced IL-6 level in plasma.…”
Section: Figure 3 |supporting
confidence: 92%
“…Previous literature on cytokine activity related to PTB and LBW have reported significant relationships between (a) IL-6 and PTB (Lucaroni et al, 2018); and (b) IL-13 and IFNÎł with LBW (Pearce et al, 2016). In our study, IL-6 showed a trend for a significant relationship with birthweight (r s = 0.388, p = 0.062) but did not show any significant correlations with the stress/emotional indicators.…”
Section: Discussioncontrasting
confidence: 48%
“…Inflammation has been used to identify dysregulation in previous AL studies and is relevant to PTB and LBW. Inadequate responses of the immune system measured at single time points (e.g., exaggerated inflammatory response measured as cytokines) in pregnant women with PTB have been previously identified (Lucaroni et al, 2018). Specifically, a systematic review authored by Lucaroni and colleagues (2018) reported increased interleukin-6 (IL-6) levels measured in maternal serum are associated with increased odds ratio of 2 (95%CI 1-3) and increased likelihood value of 12.…”
mentioning
confidence: 99%
“…The digital cervical score [12] and Bishop score [13] as predictors of SPTD have demonstrated low diagnostic accuracy (61% -68%) [14]. Even though numerous risk factors associated with SPTD have been identified in previous work, the ability to accurately predict when labor will occur remains elusive [15] [16] [17] [18]. In a well-regarded, large observational cohort study, serial transvaginal ultrasound cervical length and quantitative vaginal fetal fibronectin had low predictive accuracy for SPTD among nulliparous women [19].…”
Section: Introductionmentioning
confidence: 99%